CHARACTERIZATION OF LIMA BEAN NODULATING RHIZOBIA IN SOIL FROM THREE STATES OF BRAZILIAN NORTHEASTERN (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The aim of this study was to characterize lima bean nodulating rhizobial from soils of northeastern Brazil. Soil samples were collected in regions with production of lima bean in the Ceara, Piaui and Maranhao states. The experiment was conducted in pots containing soil from each region, sowed with lima bean. Nodules were sampled for isolation and characterization at 35 days after plant emergence. A total of 75 isolates were found and submitted to morphological and physiological characterization. Morphologically, the majority of isolates exhibited circular and convex colonies with entire border and smooth surface. Physiologically, all isolated presented fast growth, and the majority of isolates presented acid reaction, moderate ability to produce mucus with gummy consistency and colonies with cream coloration. The isolates found in this study presented similar characteristics to genera Rhizobium, Sinorhizobium,Allorhizobium eMesorhizobium.